PENGARUH KONFLIK PERAN, KONFLIK PEKERJAAN-KELUARGA DAN PEKERJAAN BERLEBIH TERHADAP KINERJA KARYAWAN PT AIR MANCUR DI WONOGIRI - Tiara Dhinar Kusumawardani Suprayitno & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2015)
This research aims to analyze the significance of the influence of the role of conflict, the work of family conflict, excess and work on employee performance. A survey conducted the research is to employees of PT Air Mancur in Wonogiri. The population in this research is all the employees in PT Air Mancur in Wonogiri with the sample as many as 76 people with clusters of proportional random sampling techniques, the results show that the role of the conflict have negative effects on employee performance and significant. Family conflict and significant work have negative effects on employee performance. Work and significant excess have negative effects on employee performance. R2 obtained adjusted the value of the coefficients determined 0,393 it means of variable influence the role of the contributions of conflict, family conflict and work is work 39,3% excess of, while the rest of 60,7% influenced by other variables that is not examined . Keywords: conflict the role of, family conflict work, excess work, employee performance